Performance management practices in the Saudi Arabian public sector - Alkahtani, Moshobab; Abdullah, Nur Anisah; Lawrie, Gavin (2013)
This paper presents findings from a recent study of performance measurement and management practices in the Saudi Arabian public sector. The study focused on use of performance data to support the implementation of strategic plans, and combined an extensive survey of current practices with follow-up work within several Saudi Arabian Government Agencies. The study is part of a wider project to test and validate a novel standardised approach to the measurement of performance of public agencies; the ultimate aim of the study being to provide a methodological foundation for the broad scale monitoring of effectiveness and productivity within the Saudi Arabian public sector. The survey instrument was distributed to 175 agencies within the Saudi Arabian public sector, and achieved a 57% response rate. Follow up studies were undertaken within seven Agencies, selection of which was influenced by the maturity of their existing performance measurement approaches as reported in the survey. The survey instrument used was based on one administered previously in the UK and Malaysia (adaptations were needed to accommodate the different political system in Saudi Arabia). By extending an existing study series, the survey findings could be compared between countries. The follow-up work carried out with the seven Agencies comprised a review of existing practices, and then activities working with the leadership of each Agency to develop improved methods of performance management and monitoring for the agency, using methods linked to the standardised approach proposed by the study for Saudi Arabian public sector organisations. The paper draws conclusions about the extent to which the survey responses are indicative of Agency preparedness to implement the proposed standardised approach, and more general conclusions about the influence of performance management maturity level on the success of the interventions made.